2018
DOI: 10.1002/erv.2660
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of a positive screen for eating disorders among Syrian refugees

Abstract: The objective of this cross‐sectional study was to examine the prevalence and correlates of a positive screen for eating disorders (EDs) in a sample of Syrian refugees living in North Lebanon. The study was conducted on a convenience sample of 450 (84.67% women and 15.33% men) refugees, aged between 18 and 45 years. The prevalence of a positive screen for ED was 5.79%. Bivariate analyses revealed that female gender (p = 0.02), presence of medical conditions (p = 0.01), old occurrence of major stressful life ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 49 publications
0
6
0
6
Order By: Relevance
“…Pandemics pose a double care burden on health care professionals (Aoun, Joundi, & El Gerges, 2019; Li et al, 2018; Raven, Wurie, & Witter, 2018). A recent study in China in health care workers (nurses, physicians) who were exposed to COVID‐19 showed that many of them were suffering from distress, depression, anxiety and insomnia (Lai et al, 2020).…”
Section: Therapist and Staff Working In Edmentioning
confidence: 99%
“…Pandemics pose a double care burden on health care professionals (Aoun, Joundi, & El Gerges, 2019; Li et al, 2018; Raven, Wurie, & Witter, 2018). A recent study in China in health care workers (nurses, physicians) who were exposed to COVID‐19 showed that many of them were suffering from distress, depression, anxiety and insomnia (Lai et al, 2020).…”
Section: Therapist and Staff Working In Edmentioning
confidence: 99%
“…Forty-two studies assessed PTSD and trauma-related disorders (Acarturk et al, 2018, 2021; Alpak et al, 2015; Al-Smadi et al, 2016; Aoun et al, 2019; Basheti et al, 2019; Böge et al, 2020; Borho et al, 2020; Cengiz et al, 2018; Cheung Chung et al, 2018; Chung & Shakra, 2022; Chung et al, 2017, 2021; Chung, AlQarni et al, 2018; Chung, Shakra et al, 2018; Demir et al, 2020; Ersahin, 2022; Fuhr et al, 2019; Georgiadou et al, 2018, 2020; Gottvall et al, 2019; Hendaus et al, 2021; Ibrahim & Hassan, 2017; Javanbakht et al, 2019; Jefee-Bahloul et al, 2014; Kazour et al, 2017; Mahmood et al, 2019; Marwa, 2016; McGrath et al, 2020; M’zah et al, 2019; Oda et al, 2021; Powell et al, 2020; Rizkalla & Segal, 2018, 2019; Röhr et al, 2020; Sagaltici et al, 2020; Sengoelge et al, 2019; Sim et al, 2018, 2019; Tekeli-Yesil et al, 2018; Tinghög et al, 2017; Uygun, 2021). The most preferred instrument to evaluate PTSD was the Harvard Trauma Questionnaire (HTQ).…”
Section: Prevalence Risk Factors and Assessment Methods For Psychiatr...mentioning
confidence: 99%
“…Only one study in this review assessed psychosis, and it reported a positive screening of 7.6% for psychotic disorders using the Mini International Neuropsychiatric Interview (MINI) instrument (Rizkalla & Segal, 2018). Other mental disorders or psychiatric symptoms investigated were psychological distress (Basheti et al, 2015; Borho et al, 2020; Bridekirk & Hynie, 2021; Hendaus et al, 2021; Khamis, 2022; M’zah et al, 2019; Oda et al, 2021; Saab et al, 2020; Schlechter et al, 2021; Sim et al, 2018, 2019), somatization problems (Braun-Lewensohn et al, 2019; Cheung Chung et al, 2018; Chung & Shakra, 2022; Chung et al, 2017, 2021; Chung, AlQarni et al, 2018; Chung, Shakra et al, 2018; McGrath et al, 2020), substance use disorders (Kazour et al, 2017; Oda et al, 2021), and eating disorder (Aoun et al, 2019).…”
Section: Prevalence Risk Factors and Assessment Methods For Psychiatr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Parameter estimation is the objective of epidemiological studies conducted to find out the frequency of an event in a certain population, for example, studies aiming at assessing the prevalence (also risk or rate) of disorders, symptoms or exposure to specific risk factors. In the ED area, epidemiological studies have been designed to solve different estimation problems, such as (a) determining the prevalence of eating problems in clinical or community populations [such as the study by Bagaric and colleagues among a community sample of South Australia looking at the lifetime prevalence of bulimia nervosa (BN) and binge ED (Bagaric, Touyz, Heriseanu, Conti, & Hay, 2020) or the study by Schulte Erica and Gearhardt, 2018 aiming at estimating the presence of food addiction in a representative sample of students of the United States; and (b) finding out the frequency of eating symptoms/problems within specific segments of populations characterized by high vulnerability [such as the study by Aoun and colleagues among a sample of Syrian refugees (Aoun, Joundi, & El Gerges, 2019)]. These primary research publications can later be included in epidemiological systematic reviews or meta-analyses, which are based on structuring and synthesizing the available empirical evidence in order to answer a specific research question.…”
Section: Introductionmentioning
confidence: 99%